Real-world andexanet alfa utilization and the association between delay in administration due to hospital transfer and all-cause inpatient mortality - Huiqiao Fan; Youssef Bessada; Craig I. Coleman (Research and Practice in Thrombosis and Haemostasis)
Background: Evaluations of andexanet alfa for the reversal of factor Xa inhibitor-associated bleeding have been small, with cohorts drawn from single/limited sites. Delays in providing anticoagulation reversal due to hospital transfer may result in poorer outcomes. Objectives: To describe the characteristics and outcomes of andexanet alfa users and evaluate the association between delay in andexanet alfa administration due to transfer from a different acute care hospital and the incidence of all-cause inpatient mortality. Methods: This was a retrospective study using National Inpatient Sample data. Hospitalizations with procedural codes for andexanet alfa and a billing code for bleeding were included. Descriptive analysis was performed, as was multivariable logistic regression, to estimate the odds ratio and 95% CI for the association between andexanet alfa delayed due to transfer from a different acute care hospital and all-cause inpatient mortality. Results: From 2019 to 2021, 4210 hospitalizations occurred in adults receiving andexanet alfa and a bleed. Most were hospitalized with intracranial hemorrhage (62.0%). The incidence of all-cause inpatient mortality was 16.6% (95% CI, 14.3%-19.3%), mean hospital stays lasted 9.1 days (95% CI, 8.4-9.8), and mean hospital costs were $73,600 (95% CI, $65,000-$82,200). Of all cases, 18.5% were transferred from a different acute care hospital prior to receiving andexanet alfa. Cases with hospital transfer had an 82% increased odds of all-cause inpatient mortality (95% CI, 17%-183%) but did not reach statistical significance when the population was limited to intracranial hemorrhage (odds ratio, 1.51; 95% CI, 0.88-2.60). Conclusion: Delay in administering andexanet alfa due to hospital transfer may be associated with increased all-cause mortality.